PENYULUHAN KEWIRAUSAHAAN DAN PEMBERDAYAAN SISWA YATIM PIATU DI CIPUTAT TANGERANG SELATAN BANTEN - Lies Sunarmintyastuti; Hugo Aries Suprapto; Loecita Sandiar; Ari Wahyu Leksono; Sigit Widiyarto (ABIDUMASY, 2020)
Abstract:Entrepreneurship is a field that is still less attractive to adolescents. But the efforts that have been carried out by the government and the private sector have been many. It still needs the support of many parties, including community service activities carried out in Islamic boarding schools. The purpose of community service activities is to instill entrepreneurial values early on in students. It is hoped that in the future students will become reliable and professional entrepreneurs. This activity was carried out from April to July 2020. The method used was the method of practice and providing counseling and monitoring of implementation. Students who participated were orphaned students at the Ciputat Arrahman Foundation Tangerang, totaling 23 students. The results of this activity indicate that students have been able to make several souvenir models from paper. The target results for each group are 100%, 80% and 70%. Students are given the opportunity to deliver the results of their products in the pesantren environment, some are also sold in the cooperative and to the surrounding community. Community response to the results of the students good and positive Keywords: Entrepreneurship, Empowerment, Orphans Abstrak:Kewirausahaan merupakan bidang yang masih kurang diminati oleh kalangan remaja. Namun upaya yang sudah dilaksanakan oleh pemerintah dan pihak swasta sudah banyak. Masih perlu dukungan banyak pihak,termasuk kegiatan pengabdian masyarakadilakukan di pondok pesantren. Tujuan kegiatan pengabdian kepada masyarakat ini untuk menanamkan nilai – nilai kewirausahaan sejak dini pada siswa. Diharapkan pada waktu yang akan datang para siswa menjadi wirausahawan yang handal dan professional. Kegiatan ini dilaksanakan dari bulan April sampai dengan Juli 2020. Metode yang digunakan adalah metode praktek dan pemberian penyuluhan serta monitoring pelaksanaan. Siswa yang ikut adalah siswa yatim piatu pada yayasan Arrahman Ciputat Tangerang, sebanyak 23 siswa. Hasil kegiatan ini menunjukkan bahwa siswa sudah mapu membuat beberapa model souvenir dari kertas. Hasil target masing – masing kelompok sebesar 100%, 80 % dan 70%. Siswa diberikan kesempatan untuk meamsarkan hasil produk mereka di dalam lingungan pesantren, sebagian juga dijual dikoperasi dan kepada masyarakat sekitar. Respon masyarakat kepada hasil dari para santriwan baik dan positif. Kata Kunci : Kewirausahaan, Pemberdayaan, siswa Yatim Piatu